PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN SERTIFIKASI PENDIDIK GURU SMP DI KABUPATEN MURUNG RAYA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Jadiaman Parhusip (Universitas Palangka Raya, 2020)
Means of government to improve quality of teacher is accomplished through teacher certification. It is done by selecting every teacher listed in Education Board in Indonesia. Lots of data of participants of the teacher certification and confusion of criteria in selection of the teacher certification done by committee of the teacher certification can cause inaccurate data of the eligible participants to be certified. It causes gap for teacher which is actually eligible to be certified. To overcome the situation, it is necessary to produce a computer-based systematic effort for every working unit, in this case is Education Board of Murung Raya Regency in Central Kalimantan. The Development of Decision Support System which was used in this study was started by analyzing available system and analyzing related literature, Government Regulations, which was used as legal foundation to process data related to the teacher certification. Teacher certification scoring used Simple Additive Weighting (SAW), which scored every datum and then was normalized by matrix. The result of matrix normalization obtained the final score of 7 (seven) criteria for every teacher which later will be ranked from the highest to the lowest. The rank was utilized to decide priority of teacher which was eligible to be certified. This application used Borland Delphi 7 as the programming language and MySQL as the database engine. The result of this study was a helping application to recommend teacher certification. Data which was produced by the application showed the similar result compared with the result of manual scoring from the institution. Therefore, it is suggested to implement the application since it is really helpful to assist the Education Board of Murung Raya, especially for employment construction to decide priority teacher to get the certification for every year as long as the regulation or policy does not change.